An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Fine particulate matter composition in American Indian vs. Non-American Indian communities - Maggie Li; Vivian Do; Jada L. Brooks; Markus Hilpert; Jeff Goldsmith; Steven N. Chillrud; Tauqeer Ali; Lyle G. Best; Joseph Yracheta; Jason G. Umans; Aaron van Donkelaar; Randall V. Martin; et al. (Environmental Research, 2023)

Deep diving by offshore bottlenose dolphins ( Tursiops spp.) - Andreas Fahlman; Reny B. Tyson Moore; Rae Stone; Jay Sweeney; Robyn Faulkner Trainor; Aaron A. Barleycorn; Katherine McHugh; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
We used satellite‐linked tags to evaluate dive behavior in offshore bottlenose dolphins ( Tursiops spp.) near the island of Bermuda. The data provide evidence that bottlenose dolphins commonly perform both long (>272 s) and deep (>199 m) dives, with the deepest and longest dives being to 1,000 m and 826 s (13.8 min), respectively. The data show a relationship between dive duration and dive depth for dives longer than about 272 s. There was a diurnal pattern to dive behavior, with most dives deeper than 50 m being performed at night; deep diving began at sunset and varied throughout the night. We used the cumulative frequency of dive duration to estimate a behavioral aerobic dive limit (bADL) of around 560–666 s (9.3–11.1 min) in adult dolphins in this population. Dives exceeding the bADL spent significantly longer time in the upper‐most 50 m following a dive as compared with dives less than the bADL. We conclude that the offshore ecotype off Bermuda, unlike the shallow‐diving near‐shore bottlenose dolphin, is a deep‐diving ecotype, and may provide a useful animal model to study extreme diving behavior and adaptations.

The fitness consequences of human‐wildlife interactions on foraging common bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida - Kylee M. DiMaggio; Miguel A. Acevedo; Katherine A. McHugh; Krystan A. Wilkinson; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
Human‐wildlife interactions (HI) are becoming more prevalent with increasing human population. These interactions could have important eco‐evolutionary consequences that become apparent only after observing populations for multiple generations. Here, we analyzed 28 years (1993–2020) of data from the world's longest‐running study of a wild dolphin population to assess the fitness consequences of HI on common bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida. We investigated how human‐related foraging activities such as depredation, begging, and patrolling mediate reproductive output and reproductive success of conditioned (HI) and unconditioned (non‐HI) females. The analysis of 84 females and their 286 calves born during 1993–2020 found a confluence of effects on individual fitness. Reproductive output of females engaging in moderate levels of human‐related foraging was 94% greater than that of non‐HI females. However, high frequencies of human‐related foraging had a negative effect on female reproductive success by increasing the risk of calf death up to nine times when compared to non‐HI females, resulting in 31% less calf survival. These findings provide evidence that human‐wildlife interactions have considerable potential to catalyze population‐level changes by altering individual fitness, and demonstrate the value of comprehensive, long‐term data to better understand the ecological and evolutionary implications of human‐wildlife conflict.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Surface and diving metabolic rates, and dynamic aerobic dive limits ( dADL ) in near‐ and off‐shore bottlenose dolphins, Tursiops spp., indicate that deep diving is energetically cheap - Andreas Fahlman; Austin S. Allen; Ashley Blawas; Jay Sweeney; Rae Stone; Robyn Faulkner Trainor; Frants H. Jensen; Katherine McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2023)
High‐resolution dive depth and acceleration recordings from nearshore (Sarasota Bay, dive depth Tursiops spp.) were used to estimate the diving metabolic rate (DMR) and the locomotor metabolic rate (LMR, L O 2 /min) during three phases of diving (descent, bottom, and ascent). For shallow dives (depth ≤ 30 m), we found no differences between the two ecotypes in the LMR during diving, nor during the postdive shallow interval between dives. For intermediate (30 m 100 m), the LMR was significantly higher during ascent than during descent and the bottom phase by 59% and 9%, respectively. In addition, the rate of change in depth during descent and ascent (meters/second) increased with maximal dive depth. The dynamic aerobic dive limit (dADL) was calculated from the estimated DMR and the estimated predive O 2 stores. For the Bermuda dolphins, the dADL decreased with dive depth, and was 18.7, 15.4, and 11.1 min for shallow, intermediate, and deep dives, respectively. These results provide a useful approach to understand the complex nature of physiological interactions between aerobic metabolism, energy use, and diving capacity.

Unveiling mesophotic diversity in Hawai‘i: two new species in the genera Halopeltis and Leptofauchea (Rhodymeniales, Rhodophyta) - Erika A. Alvarado; Feresa P. Cabrera; Monica O. Paiano; James T. Fumo; Heather L. Spalding; Celia M. Smith; Jason C. Leonard; Keolohilani H. Lopes Jr.; Randall K. Kosaki; Alison R. Sherwood (Algae, 2022)
Two genera of the Rhodymeniales, Halopeltis and Leptofauchea, are here reported for the first time from the Hawaiian Islands and represent the deepest records for both genera. Molecular phylogenetic analyses of cytochrome oxidase subunit I (COI), rbcL, and large subunit ribosomal DNA (LSU) sequences for Hawaiian specimens of Leptofauchea revealed one well-supported clade of Hawaiian specimens and three additional lineages. One of these clades is described here as Leptofauchea huawelau sp. nov., and is thus far known only from mesophotic depths at Penguin Bank in the Main Hawaiian Islands. L. huawelau sp. nov. is up to 21 cm, and is the largest known species. An additional lineage identified in the LSU and rbcL analyses corresponds to the recently described L. lucida from Western Australia, and is a new record for Hawai‘i. Hawaiian Halopeltis formed a well-supported clade along with H. adnata from Korea, the recently described H. tanakae from mesophotic depths in Japan, and H. willisii from North Carolina, and is here described as Halopeltis nuahilihilia sp. nov. H. nuahilihilia sp. nov. has a distinctive morphology of narrow vegetative axes that harbor constrictions along their length. The current distribution of H. nuahilihilia includes mesophotic depths around W. Maui, W. Moloka‘i, and the island of Hawai‘i in the Main Hawaiian Islands. Few reproductive characters were observed because of the small number of specimens available; however, both species are distinct based on phylogeny and morphology. These descriptions further emphasize the Hawaiian mesophotic zone as a location harboring many undescribed species of marine macroalgae.

Anatomical, Ontogenetic, and Genomic Homologies Guide Reconstructions of the Teeth-to-Baleen Transition in Mysticete Whales - John Gatesy; Eric G. Ekdale; Thomas A. Deméré; Agnese Lanzetti; Jason Randall; Annalisa Berta; Joseph J. El Adli; Mark S. Springer; Michael R. McGowen (Journal of Mammalian Evolution, 2022)

Corrigendum: Rise of the machines: Best practices and experimental evaluation of computer-assisted dorsal fin image matching systems for bottlenose dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Rise of the Machines: Best Practices and Experimental Evaluation of Computer-Assisted Dorsal Fin Image Matching Systems for Bottlenose Dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)
Photographic-identification (photo-ID) of bottlenose dolphins using individually distinctive features on the dorsal fin is a well-established and useful tool for tracking individuals; however, this method can be labor-intensive, especially when dealing with large catalogs and/or infrequently surveyed populations. Computer vision algorithms have been developed that can find a fin in an image, characterize the features of the fin, and compare the fin to a catalog of known individuals to generate a ranking of potential matches based on dorsal fin similarity. We examined if and how researchers use computer vision systems in their photo-ID process and developed an experiment to evaluate the performance of the most commonly used, recently developed, systems to date using a long-term photo-ID database of known individuals curated by the Chicago Zoological Society’s Sarasota Dolphin Research Program. Survey results obtained for the “Rise of the machines – Application of automated systems for matching dolphin dorsal fins: current status and future directions” workshop held at the 2019 World Marine Mammal Conference indicated that most researchers still rely on manual methods for comparing unknown dorsal fin images to reference catalogs of known individuals. Experimental evaluation of the finFindR R application, as well as the CurvRank, CurvRank v2, and finFindR implementations in Flukebook suggest that high match rates can be achieved with these systems, with the highest match rates found when only good to excellent quality images of fins with average to high distinctiveness are included in the matching process: for the finFindR R application and the CurvRank and CurvRank v2 algorithms within Flukebook more than 98.92% of correct matches were in the top 50-ranked positions, and more than 91.94% of correct matches were returned in the first ranked position. Our results offer the first comprehensive examination into the performance and accuracy of computer vision algorithms designed to assist with the photo-ID process of bottlenose dolphins and can be used to build trust by researchers hesitant to use these systems. Based on our findings and discussions from the “Rise of the Machines” workshop we provide recommendations for best practices for using computer vision systems for dorsal fin photo-ID.

Assessing the Viability of the Sarasota Bay Community of Bottlenose Dolphins - Robert C. Lacy; Randall S. Wells; Michael D. Scott; Jason B. Allen; Aaron A. Barleycorn; Kim W. Urian; Suzanne Hofmann (Frontiers in Marine Science, 2021)
Population models, such as those used for Population Viability Analysis (PVA), are valuable for projecting trends, assessing threats, guiding environmental resource management, and planning species conservation measures. However, rarely are the needed data on all aspects of the life history available for cetacean species, because they are long-lived and difficult to study in their aquatic habitats. We present a detailed assessment of population dynamics for the long-term resident Sarasota Bay common bottlenose dolphin ( Tursiops truncatus ) community. Model parameters were estimated from 27 years of nearly complete monitoring, allowing calculation of age-specific and sex-specific mortality and reproductive rates, uncertainty in parameter values, fluctuation in demographic rates over time, and intrinsic uncertainty in the population trajectory resulting from stochastic processes. Using the Vortex PVA model, we projected mean population growth and quantified causes of variation and uncertainty in growth. The ability of the model to simulate the dynamics of the population was confirmed by comparing model projections to observed census trends from 1993 to 2020. When the simulation treated all losses as deaths and included observed immigration, the model projects a long-term mean annual population growth of 2.1%. Variance in annual growth across years of the simulation ( SD = 3.1%) was due more to environmental variation and intrinsic demographic stochasticity than to uncertainty in estimates of mean demographic rates. Population growth was most sensitive to uncertainty and annual variation in reproduction of peak breeding age females and in calf and juvenile mortality, while adult survival varied little over time. We examined potential threats to the population, including increased anthropogenic mortality and impacts of red tides, and tested resilience to catastrophic events. Due to its life history characteristics, the population was projected to be demographically stable at smaller sizes than commonly assumed for Minimum Viable Population of mammals, but it is expected to recover only slowly from any catastrophic events, such as disease outbreaks and spills of oil or other toxins. The analyses indicate that well-studied populations of small cetaceans might typically experience slower growth rates (about 2%) than has been assumed in calculations of Potential Biological Removal used by management agencies to determine limits to incidental take of marine mammals. The loss of an additional one dolphin per year was found to cause significant harm to this population of about 150 to 175 animals. Beyond the significance for the specific population, demographic analyses of the Sarasota Bay dolphins provide a template for examining viability of other populations of small cetaceans.

Community Science for Coastal Acidification Monitoring and Research - Parker Randall Gassett; Katie O’Brien-Clayton; Carolina Bastidas; Jennie E. Rheuban; Christopher, W. Hunt; Elizabeth Turner; Matthew Liebman; Emily Silva; Adam, R. Pimenta; Jason. Grear; Jackie Motyka; Daniel McCorkle; et al. (Coastal Management, 2021)

Staying Alive: Long-Term Success of Bottlenose Dolphin Interventions in Southwest Florida - Katherine A. McHugh; Aaron A. Barleycorn; Jason B. Allen; Kim Bassos-Hull; Gretchen Lovewell; Denise Boyd; Anna Panike; Carolyn Cush; Deborah Fauquier; Blair Mase; Robert C. Lacy; Michelle R. Greenfield; et al. (Frontiers in Marine Science, 2021)
Small cetaceans face persistent threats from fisheries interactions, making effective mitigation a priority for conservation. In southwest Florida, interactions come primarily from small-scale recreational hook and line and trap/pot fisheries, with regional stranding network partners working with federal agency managers to assess and intervene as possible in cases of live animal entanglement. Evaluating success of intervention cases is difficult due to financial and logistical constraints which may preclude detailed follow-up monitoring. Survival over the initial 6 weeks post-release has been used as a marker of short-term success for small-cetacean rescue and/or rehabilitation cases. Early intervention prior to stranding, especially via remote disentanglement or rescue and immediate re-release onsite, can save entangled free-ranging dolphins facing life-threatening anthropogenic injuries. However, given the costs associated with interventions, it is important to understand the benefits of these endeavors not only to save individuals, but also to establish if and how saved individuals contribute to social functioning, survival and reproduction within small, resident populations facing multiple concurrent threats. Here we provide evidence from 27 well-documented common bottlenose dolphin ( Tursiops truncatus ) intervention cases during 1985–2019 where follow-up monitoring over multiple years sheds light on the longer-term success of these efforts and potential benefits to local populations. Nearly all rescued individuals (92%) survived longer than 6 weeks post-release (mean minimum survival period = 5 years, range 0–35 years), with 13 still observed frequently within their prior resident communities, in good physical health, and engaging in normal behavior. Survivorship rates did not decline substantially between 1 and 5 years post-rescue, meaning survival beyond 1 year may be a useful benchmark of long-term success. Rescued females that reached reproductive maturity ( n = 4) have produced 12 post-intervention offspring to date. Social network analysis and demographic modeling applied to cases from the long-term resident community in Sarasota Bay confirmed that animals maintain social connections post-intervention and that interventions result in higher population growth rates. While not every intervention succeeds, this study demonstrates the conservation value of pre-stranding interventions which allow individuals that otherwise would be lost to remain viable and productive members of local populations when prevention of anthropogenic injury is not possible.

Improved methods for detecting Xylella fastidiosa in pecan and related Carya species - Angelyn Hilton; Xinwang Wang; Minling Zhang; Kimberly Cervantes; Jason French; Jennifer J. Randall; Clive H. Bock; L. J. Grauke; Young-Ki Jo (European Journal of Plant Pathology, 2020)

Agriculture-related Injuries: Discussion in Canadian Media - Jason R. Randall; Leo Pennetta De Oliveira; Kathy Belton; Don Voaklander (Journal of Agromedicine, 2020)

Nested association mapping of important agronomic traits in three interspecific soybean populations - Eduardo Beche; Jason D. Gillman; Qijian Song; Randall Nelson; Tim Beissinger; Jared Decker; Grover Shannon; Andrew M. Scaboo (Theoretical and Applied Genetics, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Seasonal, interannual and decadal drivers of tree and grass productivity in an Australian tropical savanna - Caitlin E. Moore; Jason Beringer; Randall J. Donohue; Bradley Evans; Jean‐François Exbrayat; Lindsay B. Hutley; Nigel J. Tapper (Global Change Biology, 2018)
Tree–grass savannas are a widespread biome and are highly valued for their ecosystem services. There is a need to understand the long‐term dynamics and meteorological drivers of both tree and grass productivity separately in order to successfully manage savannas in the future. This study investigated the interannual variability ( IAV ) of tree and grass gross primary productivity ( GPP ) by combining a long‐term (15 year) eddy covariance flux record and model estimates of tree and grass GPP inferred from satellite remote sensing. On a seasonal basis, the primary drivers of tree and grass GPP were solar radiation in the wet season and soil moisture in the dry season. On an interannual basis, soil water availability had a positive effect on tree GPP and a negative effect on grass GPP . No linear trend in the tree–grass GPP ratio was observed over the 15‐year study period. However, the tree–grass GPP ratio was correlated with the modes of climate variability, namely the Southern Oscillation Index. This study has provided insight into the long‐term contributions of trees and grasses to savanna productivity, along with their respective meteorological determinants of IAV .

Climate change impacts on selected global rangeland ecosystem services - Randall B. Boone; Richard T. Conant; Jason Sircely; Philip K. Thornton; Mario Herrero (Global Change Biology, 2018)
Rangelands are Earth's dominant land cover and are important providers of ecosystem services. Reliance on rangelands is projected to grow, thus understanding the sensitivity of rangelands to future climates is essential. We used a new ecosystem model of moderate complexity that allows, for the first time, to quantify global changes expected in rangelands under future climates. The mean global annual net primary production ( NPP ) may decline by 10 g C m −2 year −1 in 2050 under Representative Concentration Pathway ( RCP ) 8.5, but herbaceous NPP is projected to increase slightly (i.e., average of 3 g C m −2 year −1 ). Responses vary substantially from place‐to‐place, with large increases in annual productivity projected in northern regions (e.g., a 21% increase in productivity in the US and Canada) and large declines in western Africa (−46% in sub‐Saharan western Africa) and Australia (−17%). Soil organic carbon is projected to increase in Australia (9%), the Middle East (14%), and central Asia (16%) and decline in many African savannas (e.g., −18% in sub‐Saharan western Africa). Livestock are projected to decline 7.5 to 9.6%, an economic loss of from $9.7 to $12.6 billion. Our results suggest that forage production in Africa is sensitive to changes in climate, which will have substantial impacts on the livelihoods of the more than 180 million people who raise livestock on those rangelands. Our approach and the simulation tool presented here offer considerable potential for forecasting future conditions, highlight regions of concern, and support analyses where costs and benefits of adaptations and policies may be quantified. Otherwise, the technical options and policy and enabling environment that are needed to facilitate widespread adaptation may be very difficult to elucidate.

100% endemism in mesophotic reef fish assemblages at Kure Atoll, Hawaiian Islands - Randall K. Kosaki; Richard L. Pyle; Jason C. Leonard; Brian B. Hauk; Robert K. Whitton; Daniel Wagner (Marine Biodiversity, 2017)

Influence of temperature and oxygen on the distribution of blue marlin ( Makaira nigricans ) in the Central Pacific - Aaron B. Carlisle; Randall E. Kochevar; Martin C. Arostegui; James E. Ganong; Michael Castleton; Jason Schratwieser; Barbara A. Block (Fisheries Oceanography, 2017)
The blue marlin ( Makaira nigricans ) is a highly migratory pelagic predator of tropical and subtropical seas. Information on the habitat use of marine species is fundamental to understanding their ecology and population dynamics and is needed to inform responsible management strategies. Using a long‐term satellite tagging data set from The International Game Fish Association Great Marlin Race, we examined habitat use and how oxygen and temperature influence the horizontal and vertical distributions of blue marlin in the Central Pacific. Blue marlin primarily occurred in warm waters (26–30°C) and exhibited a diel bimodal depth distribution across the 5‐year data record (2009–2013), with fish spending the majority of their time near the surface at night and at deeper depths during the day (25–100 m). The depth distribution of blue marlin was limited in areas where low oxygen and/or temperature conditions occur closer to the surface, with the extent of habitat compression being greatest when both oxygen and temperature were limiting. The migrations of blue marlin appeared restricted during the 2010 La Niña, when increased equatorial upwelling resulted in an extension of the cold, low oxygen waters of the cold tongue into the Central Pacific, creating a barrier to the trans‐equatorial migrations that occurred during all other tagging years. If the frequency and intensity of La Niña events increases and the oxygen minimum layer continues to expand as has been predicted under certain climate change scenarios, the migratory behavior and habitat availability of blue marlin may be impacted.

Carcass‐recovery rates for resident bottlenose dolphins in Sarasota Bay, Florida - Randall S. Wells; Jason B. Allen; Gretchen Lovewell; Jay Gorzelany; Ruth E. Delynn; Deborah A. Fauquier; Nélio B. Barros (Marine Mammal Science, 2015)

Role of MT1 melatonin receptors in methamphetamine-induced locomotor sensitization in C57BL/6 mice - Anthony J. Hutchinson; Jason Ma; Jiabei Liu; Randall L. Hudson; Margarita L. Dubocovich (Psychopharmacology, 2014)

Severe Karenia brevis red tides influence juvenile bottlenose dolphin ( Tursiops truncatus ) behavior in Sarasota Bay, Florida - Katherine A. McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2011)
Harmful algal blooms (HABs) are natural stressors in the coastal environment that may be increasing in frequency and severity. This study investigates whether severe red tide blooms, caused by Karenia brevis , affect the behavior of resident coastal bottlenose dolphins in Sarasota Bay, Florida through changes to juvenile dolphin activity budgets, ranging patterns, and social associations. Behavioral observations were conducted on free‐ranging juvenile dolphins during the summer months of 2005–2007, and behavior during red tide blooms was compared to periods of background K. brevis abundance. We also utilized dolphin group sighting data from 2004 to 2007 to obtain comparison information from before the most severe recent red tide of 2005 and incorporate social association information from adults in the study area. We found that coastal dolphins displayed a suite of behavioral changes associated with red tide blooms, including significantly altered activity budgets, increased sociality, and expanded ranging behavior. At present, we do not fully understand the mechanism behind these red tide‐associated behavioral effects, but they are most likely linked to underlying changes in resource availability and distribution. These behavioral changes have implications for more widespread population impacts, including increased susceptibility to disease outbreaks, which may contribute to unusual mortality events during HABs.

Optimization of square-wave electroporation for transfection of porcine fetal fibroblasts - Jason W. Ross; Jeffrey J. Whyte; Jianguo Zhao; Melissa Samuel; Kevin D. Wells; Randall S. Prather (Transgenic Research, 2010)

Consequences of injuries on survival and reproduction of common bottlenose dolphins ( Tursiops truncatus ) along the west coast of Florida - Randall S. Wells; Jason B. Allen; Suzanne Hofmann; Kim Bassos‐Hull; Deborah A. Fauquier; Nélio B. Barros; Ruth E. DeLynn; Gretchen Sutton; Victoria Socha; Michael D. Scott (Marine Mammal Science, 2008)
Accurate identification of human‐induced injuries that lead to death or interfere with reproduction is important for marine mammal management, as deaths exceeding established limits can lead to restrictions on fisheries or vessel operations. The fates of cetaceans last seen swimming with attached gear, particularly in pelagic fisheries, or with vessel strike lacerations, have been difficult to predict. Survival and reproduction data from long‐term research on resident common bottlenose dolphins near Sarasota, Florida were examined relative to consequences of fishing gear ingestion, line entanglements, vessel strikes, and amputations of unknown origins. Fishing hooks embedded in the throat, goosebeak, or esophagus, or line wrapped around the goosebeak, generally lead to death. Multiple, constrictive line wraps around fin insertions can lead to amputation, blood loss, impaired mobility, or infection. Dolphins with ingested gear or severe entanglements may swim away with the gear, but likely die later. Propeller injuries involving only soft tissue were often survivable. Some dolphins survived amputations of the distal ends of fins, and continued to reproduce. As a precautionary approach, dolphins with ingested gear or severe constrictive entanglements should be considered mortalities, but extrapolations of findings from coastal bottlenose dolphins to other cetaceans and different gear must be done with caution.

Three-dimensional reconstruction of the flow in a human left heart by using magnetic resonance phase velocity encoding - Peter G. Walker; Gregory B. Cranney; Randall Y. Grimes; Jason Delatore; Joseph Rectenwald; Gerald M. Pohost; Ajit P. Yoganathan (Annals of Biomedical Engineering, 1995)